Performance and cost-benefit evaluation of farmer-managed solar-powered groundwater irrigation in Attapeu Province, Lao PDR: interim results from the first year of operation of four pilot systems - Douangsavanh, Somphasith; Pavelic, Paul; Kotchofa, Pacem; Dubois, Mark (International Water Management Institute, 2025)
As part of the previous CGIAR Initiative on Agroecology, a solar-powered groundwater irrigation system was introduced in Attapeu Province, Lao PDR. This system is managed by local farmers and was designed to help small-scale farmers overcome water shortages, improve crop productivity, and build resilience to climate change. To evaluate its effectiveness, this study reviews the system’s performance after one year of operation and a full crop cycle, including broader benefits such as environmental sustainability and a basic financial cost-benefit analysis. At this stage, the report presents interim results and does not focus heavily on detailed economic analysis in monetary terms, as the system is still in its early phase. Instead, it highlights qualitative benefits, including non-financial advantages related to environmental sustainability and other positive impacts. The report also identifies opportunities for future interventions that could work together with this system at larger landscape and basin levels, supporting the idea of “multifunctional landscapes” through integrated approaches. Overall, the solar irrigation system has shown promising results: environmentally, it helped farmers manage climate variability and grow crops during dry periods; socially, it improved water access for households and farming, reduced the burden on women and children, and strengthened community cooperation; economically and nutritionally, it lowered costs by removing electricity expenses and enabled year-round vegetable farming, which improved food security and livelihoods. In terms of sustainable water management, the creation of water user groups, along with rules, monitoring tools, and hydrological studies, supported better protection of wetlands and the wider landscape. These efforts improved understanding of water flow and provided useful insights for future wetland water use regulations, while the monitoring system will help prevent long-term negative impacts from groundwater extraction.